Economic Integration as a Factor in the Development of International Transport Corridors: Prospects for the Development of Itc North-South from the Point of View of International Law (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In order for international transport corridors to function as efficiently as possible, it is important that the states along which the corridor passes have legal relations not only in the field of transport, but on all issues, to one degree or another, related to the transportation of goods and passengers. In this paper, the author studies the issue of legal regulation and functioning of international transport corridors within the framework of the economic integration of the EU and ASEAN in order to identify the necessary legal framework for the successful functioning of the corridors. Studies show that international transport corridors cannot function effectively in the absence of economic integration, as can be seen in the example of the International transport corridor “North-South”. It is this corridor, legally founded back in 2000, due to the lack of international agreements adopted for the purpose of economic integration between the participating countries, that still does not function at the proper level. The author concludes that for the effective functioning of the International transport corridors, it is necessary to have multilateral agreements aimed at economic integration between the states through which the corridor passes.